2015
DOI: 10.1016/j.expneurol.2015.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine reduces intracerebral hemorrhage-induced white matter damage in aged rats

Abstract: Iron contributes to c-Jun N-terminal kinases (JNK) activation in young rats and white matter injury in piglets after intracerebral hemorrhage (ICH). In the present study, we examined the effect of deferoxamine on ICH-induced white matter injury and JNK activation and in aged rats. Male Fischer 344 rats (18 months old) had either an intracaudate injection of 100 µl of autologous blood or a needle insertion (sham). The rats were treated with deferoxamine or vehicle with different regimen (dosage, duration and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
1
37
1
Order By: Relevance
“…The efficacy of free radical scavengers has provided direct evidence for a causal relationship between ROS and ICH injury. Specifically, overexpression of copper/zinc-superoxide dismutase (Wakai, et al, 2014) or treatment with deferoxamine (Cui, et al, 2015, Ni, et al, 2015, H. Wu, et al, 2011), a chelator of pro-oxidative iron, significantly reduced brain injury in animal models of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of free radical scavengers has provided direct evidence for a causal relationship between ROS and ICH injury. Specifically, overexpression of copper/zinc-superoxide dismutase (Wakai, et al, 2014) or treatment with deferoxamine (Cui, et al, 2015, Ni, et al, 2015, H. Wu, et al, 2011), a chelator of pro-oxidative iron, significantly reduced brain injury in animal models of ICH.…”
Section: Discussionmentioning
confidence: 99%
“…DFX has recently been reported to downregulate expression of p-JNK in the basal ganglia linking JNK to Fe (Ni et al, 2015). JNK is a member of the MAPK signaling pathway that is activated by cytokines and environmental stress (Weston and Davis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that ICH activated the JNK signaling pathway in WM bundles in rats. Deferoxamine, an iron chelator, reduced ICH‐induced JNK activation and white matter loss . Other reports demonstrated that suppressing P38 MAPK activation confers neuroprotection in rat intracerebral hemorrhage .…”
Section: Discussionmentioning
confidence: 94%
“…[4][5][6] Our previous work has shown that ICH-induced iron toxicity causes WM injury through c-Jun N-terminal kinase (JNK) and receptor-interacting protein kinase 1 (RIPK1) activation. 7 Because of white matter's critical role in neurotransmission, WM injury may also lead to severe sensorimotor dysfunction, neurobehavioral impairment, and cognitive disorders. 8,9 Therefore, protecting against WM injury after ICH is a pressing concern.…”
Section: Backg Rou N Dmentioning
confidence: 99%